2005
DOI: 10.1590/s0102-05362005000400021
|View full text |Cite
|
Sign up to set email alerts
|

Formas de parcelamento e fontes de adubação nitrogenada para produção de couve-da-Malásia

Abstract: A couve-da-Malásia foi introduzida no Brasil, em 1992, por possuir altos teores de vitamina A, a partir de sementes trazidas da Malásia por Dr. Warwick E. Kerr, que adotou esta nomenclatura. Além disso, é de fácil cultivo e de ciclo curto (LEE, 1982; FERREIRA et al., 2002), podendo ser facilmente cultivada em hortas domésticas o ano inteiro, tornando-se uma fonte acessível de vitamina A.Na literatura existem poucas informações referentes à nutrição mineral de brássicas. Segundo Hori (1965), estas variedades bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
0
1
1
Order By: Relevance
“…Note that the TF source showed a smaller increase in stem diameter. These results differ from the results of Zanão Júnior et al (2005) that did not obtain significant difference in relation to N sources (calcium urea and nitrate) in the production of "kale of malaysia". However, Rodrigues et al (2015) working with the application of N observed that the doses of 101 and 168 kg ha -1 of N increased the percentage of onion bulbs of larger diameter (50-75 mm).…”
Section: Resultscontrasting
confidence: 99%
“…Note that the TF source showed a smaller increase in stem diameter. These results differ from the results of Zanão Júnior et al (2005) that did not obtain significant difference in relation to N sources (calcium urea and nitrate) in the production of "kale of malaysia". However, Rodrigues et al (2015) working with the application of N observed that the doses of 101 and 168 kg ha -1 of N increased the percentage of onion bulbs of larger diameter (50-75 mm).…”
Section: Resultscontrasting
confidence: 99%
“…O processo de nitrificação que ocorre após a aplicação da uréia também acidifica o solo. Esse fato também foi comprovado por Zanão Júnior et al (2005), que observaram maiores teores de Mn e Zn tanto no solo quanto nas folhas de couveda-malásia, aliado a um pH em água do solo próximo às raízes menor com a aplicação de uréia, em detrimento do nitrato de cálcio. A acidificação da rizosfera, segundo Moraghan & Mascagni Jr. (1991), aumenta a eficiência na absorção de micronutrientes metálicos Zn, Mn, Cu e Fe, cuja disponibilidade é influenciada pelo pH.…”
Section: Resultsunclassified